Addressing inequalities in the identification and management of perinatal mental health difficulties: The perspectives of minoritised women, healthcare practitioners and the voluntary sector - Darwin, Zoe; Blower, Sarah L.; Nekitsing, Chandani; Masefield, Sarah; Razaq, Rifat; Padgett, Louise; Endacott, Charlotte; Willan, Kathryn; Dickerson, Josie (Frontiers in Global Women's Health, 2022)
Background Perinatal mental health (PMH) difficulties affect approximately one in five birthing women. If not identified and managed appropriately, these PMH difficulties can carry impacts across generations, affecting mental health and relationship outcomes. There are known inequalities in identification and management across the healthcare pathway. Whilst barriers and facilitators have been identified there is a lack of clarity about how these relate to the avoidable and unfair inequalities experienced by various groups of women. Further research is required to understand how to address inequalities in PMH. Aim To understand the key factors that enable and hinder access to PMH care for women from minoritised groups across the PMH care pathway, and how these have been affected by the COVID-19 pandemic. Methods A sequential mixed-methods approach gathered views and experiences from stakeholders in one region in northern England. This included an online survey with 145 NHS healthcare practitioners and semi-structured interviews with 19 women from ethnic minority and/or socio-economically deprived backgrounds who had experienced PMH difficulties, and 12 key informants from the voluntary and community sector workforce. Quantitative data were analysed using descriptive statistics and framework analysis was applied to qualitative data. Findings Barriers and facilitators were mapped using a socio-technical framework to understand the role of (i) processes, (ii) people (organised as women, practitioners and others), (iii) technology, and (iv) the system as a whole in deepening or alleviating inequalities. Influences that were identified as pertinent to inequalities in identification and management included provision of interpreters, digital exclusion, stigma, disempowerment, distrust of services, practitioner attitudes, data capture, representation in the workforce, narrow rules of engagement and partnership working. Stakeholder groups expressed that several barriers were further compounded by the COVID-19 pandemic. Discussion The findings highlight the need for change at the system level to tackle inequalities across the PMH care pathway. Four inter-connected recommendations were developed to enable this systems change: building emotional safety between professionals and women; making PMH a part of core healthcare business; increasing cultural competency specific to PMH; and enhanced partnership working.